Dinamika Penggunaan Ruang Car Free Day Oleh Komunitas Pecinta Hewan Kota Surakarta Studi Kasus Jalan Brigjen Slamet Riyadi Tahun 2010-2018 - Gending Gusti; Sarwono Sarwono; Yasin Yusup (GEADIDAKTIKA, 2020)
The existence of animal lovers community when the CFD of Surakarta City produced their community gathering spaces with other animal lovers communities. From 2010 to 2018 these spaces experienced a dynamic. This study aims to: (1) determine the process of production of space carried out by the animal lover community in the Surakarta City CFD (2) determine the development of production of space carried out by the animal lovers community in the City of Surakarta CFD in 2010 to 2018. The research method used in this study is a qualitative method. The research approach in this study is a spatial descriptive approach and regressive approach. Based on the results of the study it can be concluded that: (1) The gathering space of animal lover communities in Surakarta City CFD was created because it was initiated by the participation of these animal lovers communities in CFD to result in social interaction. Animal lovers community practicing spatial practice in CFD. Animal lover communities arrange in such a way as the arrangement of the gathering space of each community (conceived space) using supporting attributes such as using MMT, x-banner, cage, perch and community uniforms that create new spaces of representation. (2) The spaces created by the animal lovers community from 2010 to 2012 occupy random spaces, in 2018 a permanent pattern has been seen in one location and lined up in front of the Surakarta District Court.